HERBAL CONTRACEPTIVES: EVALUATION OF ANTIFERTILITY POTENTIAL OF HIBISCUS ROSA‑SINENSIS (LINN.) - Baghel Chauhan, Shikha; Naved, Tanveer (Asian Journal of Pharmaceutical and Clinical Research, 2018)
This review explores, evaluates, and analyzes the contraceptive potential of Hibiscus rosa-sinensis L. There are large numbers of synthetic contraceptives available in the market. These synthetic contraceptives are associated with many side effects ranging from user discomfort to toxicity. India is a land of traditional herbal medicines. People are finding and exploring the advantages associated with herbal contraceptives because of their lower side effects. Herbal contraceptives have lower cost of development as compared to modern medicine. This review explores the recent advances in development that offers many benefits for shifting the paradigm for herbal contraceptives. From times immemorial, references have been made for the plants that possess antifertility properties. This review explores the need for the development of herbal contraceptives from the plant H. rosa-sinensis L. H. rosa-sinensis L is reported to have antiovulatory activity. However, the need of the hour is to assess and carry out toxicological studies and initiate development activity for formulation development.